Web Portal Development Issues: Usability, Site Managementand Content Management - Zainal Abidin, Melissa (Universiti Teknologi Petronas, 2004)
This paper is written with the aim to present the concept of integration between usability, content management and site management in order to design an effective tourism website. The study is based on the common problems that surrounds most of the web developers such as useless contents plus poor design that did not reflect the audience needs and poor site management such as broken links and unsorted web pages that are hard to be keep track. The study will cover on the application of the usability techniques to describe what is right and what is wrong with websites seen by millions. It will also covers on how the site management and content management play important roles in achieving high usability of the website. Assessing usability through case studies and following some guidelines on achieving effective site management and good content management will be part of the methods use in this project. The findings from this study highlight the importance of these existing guidelines and the need to modify or implement some of them to suit the requirement of a good tourism website through a prototype developed in this project.